P0531CONTINUOUS HEMODIAFILTRATION WITH PMMA HEMOFILTER MODULATED COMPLEMENT ACTIVATION AND RENAL DYSFUNCTION IN A SWINE MODEL OF SEPSIS-INDUCED ACUTE KIDNEY INJURY. (6th June 2020) - Stasi, Alessandra; FRANZIN, ROSSANA; Sallustio, Fabio; Divella, Chiara; Curci, Claudia; Crovace, Antonio; Ronco, Claudio; Staffieri, Francesco; Cantaluppi, Vincenzo; De Cal, Massimo; Neri, Mauro; Lorenzin, Anna; et al.
Abstract: Background and Aims: Sepsis-induced acute kidney injury (AKI) is a growing health care problem, refractory to conventional treatments. This disease is characterized by an overwhelmed immune response against a primary insult that become responsible for renal dysfunction and poor outcome. Therapeutic strategies based on blood purification have been developed for the treatment of this disease. The use of polymethyl methacrylate (PMMA) membrane hemofilter in continuous hemodiafiltration (CHDF) modality showed better hemodynamic stability and efficient renal support in chronic dialysis maintenance. Here we investigated the efficacy of Hemofeel PMMA membrane (TORAY, Japan) in interfering with Complement activation and renal damage in a swine model of sepsis-induced AKI. Method: After 3 hours from LPS infusion, 7 hours of PMMA-CVVH treatment or 7 hours of polysulfone (PSF)-CVVH were performed. Animals were sacrificed after 24h from LPS infusion. Histologic and renal function parameters were analyzed in all pigs. Pentraxin-3 (PTX3) and C5b-9 deposits were assessed on renal biopsies. Systemic Complement activation was evaluated by Wieslab kit. Gene expression profile was obtained from isolated PBMCs by Agilent SurePrint G3 Porcine Gene Expression Microarrays. Genespring and R software were used for the analysis. Results were validated by Real-time PCR. Results: Analysis of renal biopsies from septic pigs presented increased interstitial leucocyte infiltrate, extensive collagen deposition and diffuse glomerular thrombi compared to healthy pigs (p<0.05). Confocal analysis showed extensive PTX-3 and C5-b9 deposits at tubulo-interstitial level associated with significant activation of systemic complement classical and alternative pathways (p<0.05). Interestingly, PMMA-CVVH treatment significantly reduced local and systemic complement activation, leucocyte infiltrate and tubule-interstitial fibrosis (p<0.05). On the contrary, no significant improvement was observed by PSF-CVVH treatment. Then, we compared the whole-genome gene expression profiles of swine PBMC. We identified 711 differentially expressed genes comparing PBMC before LPS infusion (LPS T0) and after 24 hours from LPS infusion (LPS T24) and 913 genes comparing gene expression profiles of LPS T24 group with that of septic pigs treated with PMMA-CVVH (PMMA T24 group) (fold change >2 ; false discovery rate <0.05). The most modulated genes were Granzime B, Complement Factor B, Complement Component 4 Binding Protein Alpha, IL-12, SERPINB-1 and TIMP-2 that were closely related to sepsis-induced immunological process. Finally, quantitative PCR confirmed the microarray data indicating that Granzime B and Complement Factor B upregulation in PBMC was significantly hampered by PMMA treatment. Conclusion: Our data suggest that LPS induced AKI is characterized by activation of Classical and alternative Complement pathways resulting in significant renal tissue damage. By interfering with complement activation and inflammatory response, PMMA membrane might prevent dysfunctional activation of resident renal cells with prevention of sepsis-induced AKI.